Mating behavior and description of immature stages of Cyclocephala melanocephala (Fabricius, 1775) (Coleoptera: Scarabaeidae: Dynastinae), identification key and remarks on known immatures of Cyclocephalini species - Rodrigues,Sérgio Roberto (2018)
ABSTRACT Mating behavior and description of immature stages of Cyclocephala melanocephala (Fabricius, 1775) (Coleoptera: Scarabaeidae: Dynastinae), identification key and remarks on known immatures of Cyclocephalini species. Some species of Cyclocephala Dejean, 1821 are regarded as rhizophagous crop pests and others as beneficial species. The objective of this work was to report the mating behavior and to describe the immature stages of C. melanocephala. The studies were developed at the Universidade Estadual de Mato Grosso do Sul in Cassilândia, Mato Grosso do Sul state, Brazil. Adults were collected with a light trap from September to December 2014 and 2015 to carry out studies of mating behavior, breeding, and descriptions of immature stages. Copulation lasted 10.4 ± 4.3 min and took place from 19:00 to 24:00 h. Some females refused males for mating and moved away from them. Regarding flight period, adults were collected in larger quantities from 20:00 to 23:00 h. Identification keys to immatures of three genera of Cyclocephalini, including several Cyclocephala species are presented.